(untitled) (Journal of Hama University, 2020)
Introduction : Main objective of obturation in endodontics is total obliteration of root canal system and development of a fluid tight seal at the apical foramen, which provides a biological environment for healing of periapical tissue. Aim of the research : The Aim of this Study is to evaluate the effect of the method of the removing of smear layer on the Quality of Apical Sealing of Root Canals Materials and Methods : The sample included 60 single teeth with single canal which were divided into 3 experimental groups ( n = 20 teeth each ) according to the smear layer removal method as following : ( group 1: ER –YAG , group 2 : XP–Endo Finisher File System, group 3 : control group ). The teeth were obturated using gutta percha and AD SEAL Sealer , and then left in wet environment until hardened . The external root surface was painted with two layers of nail polish except the most apical 2mm. The apical part was immersed in methylene blue for 24 hours . The apical sealing was measured by endoscope after making longitudinal sections . The data obtained was statistically analyzed using One-Way ANOVA and Bonferroni The results show that the teeth that we removed the smear layer in it with ER -YAG achieved The same apical sealing as the teeth in which we used XP Endo Finisher while both methods showed better apical sealing than teeth with smear layer not removed .